Defining and classifying adverse events following joint manipulation and mobilization: An international e-Delphi study and focus groups - Martha Funabashi; Lindsay M Gorrell; Katherine A Pohlman; Andrea Bergna; Nicola R Heneghan (PLoS ONE, 2025)
Spinal and peripheral joint manipulation (MAN) and mobilization (MOB) are widely used for managing musculoskeletal conditions. Although adverse events (AE) have been reported following these interventions, there is no universally accepted definition and classification system. This study aimed to establish an inter-professional and international standardized definition and severity classification for AE following MAN and MOB. This sequential mixed-methods study included an electronic Delphi process (e-Delphi) followed by focus groups. Inter-professional and international expert stakeholders participated in 3 e-Delphi rounds: Round 1 included open-ended questions on participants’ working AE definition and severity classification; Round 2, level of agreement with statements generated from Round 1 and a previous scoping review; and Round 3, level of agreement with statements achieving consensus in Round 2. Focus groups explored e-Delphi findings. Consensus was reached for severity categories (i.e., mild, moderate, severe and catastrophic) and on 2 domains to differentiate these categories (i.e., symptom intensity and impact on patient). Consensus was not reached for a standardized AE definition following MAN and MOB. Focus group discussions centered on “unfavourable”, “unexpected” and “undesired” terms and differences between “serious” and “catastrophic” severity classification categories. Findings contribute to advancing patient safety and AE knowledge across professions and informing further safety research and practice.